Means and methods of formation of organizational and managerial competence of a university teacher - Natalya V. Solovova; Natallia V. Sukhankina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article reports the findings of the pilot research that investigates the development and testing of a system of tools and methods employed for formation of organizational and managerial competence of a university teacher. The tool for organizational and managerial competence formation analyzed herein is the additional professional program, i.e. “Educational Programs Management”, implemented at the Center for the Development of Professional Competencies of Samara University. The program is aimed at the development of organizational and managerial competence components (value-motivational, cognitive, design, expert), formation of students' readiness for effective interaction in the course of design and implementation of competitive educational programs. Educational Programs Management includes four sections: Economics of education: analysis and control of the financial and economic activities of higher educational organizations; Educational program management; Economics of educational program; The quality and competitiveness of the educational program. The content of sections and subsections of the program, training methods, ensuring the development of indicators of value-motivational, cognitive, design and expert components, were selected with due respect to the structure of the organizational and managerial competence being formed. It has been revealed that it is reasonable to use the methods as follows: ways of positive motivation formation (productive learning environment; diversity and inclusion; professional and personal achievements and accomplishments, etc.); interactive teaching methods (role-playing and business games, discussions, brainstorming, case studies, trainings, etc.); methods for the development of personal educational environment (the use of personal experience of teachers, self-reflection, self-knowledge, etc.). The research has confirmed the efficiency of the developed system of tools and methods under study, which has been developed for formation of organizational and managerial competence of university teachers based on the growth of the self-esteem index of its components and changes in the dominant indicators.